Genera and Species of the Anisakidae Family and Their Geographical Distribution - Juan C. Ángeles-Hernández; Fabian R. Gómez-de Anda; Nydia E. Reyes-Rodríguez; Vicente Vega-Sánchez; Patricia B. García-Reyna; Rafael G. Campos-Montiel; Norma L. Calderón-Apodaca; Celene Salgado-Miranda; Andrea P. Zepeda-Velázquez (Animals, 2020)
Nematodes of the Anisakidae family have the ability to infest a wide variety of aquatic hosts during the development of their larval stages, mainly marine mammals, aquatic birds, such as pelicans, and freshwater fish, such crucian carp, these being the hosts where the life cycle is completed. The participation of intermediate hosts such as cephalopods, shrimp, crustaceans and marine fish, is an important part of this cycle. Due to morphological changes and updates to the genetic information of the different members of the family, the purpose of this review was to carry out a bibliographic search of the genus and species of the Anisakidae family identified by molecular tests, as well as the geographical area in which they were collected. The Anisakidae family is made up of eight different parasitic genera and 46 different species. Those of clinical importance to human health are highlighted: Anisakis pegreffi, A. simplexsensu stricto, Contracaecumosculatum, Pseudoterranova azarazi, P. cattani, P. decipiens and P. krabbei. The geographical distribution of these genera and species is located mainly in the European continent, Asia and South America, as well as in North and Central America and Australia. Based on the information collected from the Anisakidae family, it was determined that the geographical distribution is affected by different environmental factors, the host and the ability of the parasite itself to adapt. Its ability to adapt to the human organism has led to it being considered as a zoonotic agent. The disease in humans manifests nonspecifically, however the consumption of raw or semi-raw seafood is crucial information to link the presentation of the parasite with the disease. The use of morphological and molecular tests is of utmost importance for the correct diagnosis of the genus and species of the Anisakidae family.